A single-component thermally conductive gel and a preparation method thereof
By using a combination of modified boron nitride thermal filler and liquid metal in thermal conductivity gel, the problem of oil seepage in existing thermal conductivity gels at high temperatures and extrusion is solved, and the effects of excellent thermal conductivity, high extrusion rate and low oil seepage rate are achieved, meeting the demands of electronic equipment for efficient heat dissipation and high voltage resistance.
Patent Information
- Application Number
- CN202411129741.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-16
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-08-16
AI Technical Summary
Existing thermal conductivity gels may exudate silicone oil when heated and extruded by parts, resulting in damage to the equipment. Moreover, their thermal conductivity and low oil permeability are relatively average, and cannot meet the requirements of electronic equipment for heat dissipation and instantaneous high voltage resistance.
The preparation method of a single-component thermal gel is adopted, including vinyl silicone oil, side hydrogen-containing silicone oil, liquid metal and modified boron nitride thermal filler. Through the synergy between the modified boron nitride thermal filler and liquid metal, a gel with excellent thermal conductivity, high extrusion rate and low oil permeability is formed.
It achieves excellent thermal conductivity, high extrusion rate and low oil permeability, which can effectively conduct heat, improve heat conduction efficiency, and improve the stability and service life of the thermal conduction gel.
Smart Images

Figure BDA0004997464540000081
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of thermally conductive gels, and in particular to a single-component thermally conductive gel and a preparation method thereof. Background Art
[0002] With the continuous development of current science and technology digitalization and the advent of the 5G era, electronic equipment and electronic components are gradually developing towards miniaturization, precision and high power. Due to miniaturization, precision and high power, electronic equipment and electronic components will inevitably generate and accumulate a lot of heat inside them during operation. If the heat is not guided out from the inside in time, it will affect the working efficiency of the equipment and seriously affect its service life. Therefore, how to solve the heat dissipation problem of precision equipment has become a top priority.
[0003] However, existing thermally conductive gels may leak silicone oil when heated and parts are squeezed, causing damage to the equipment. In addition, the thermal conductivity and low oil permeability of existing thermally conductive gels are relatively general, and cannot meet the requirements of constantly updated electronic equipment for heat dissipation and transient high voltage resistance. Summary of the invention
[0004] The purpose of the present application is to provide a one-component thermally conductive gel and a preparation method thereof in view of the deficiencies of the current technology. The one-component thermally conductive gel prepared in the present application has the advantages of excellent thermal conductivity, high extrusion rate and low oil permeability.
[0005] In a first aspect, the present application provides a single-component thermally conductive gel, which adopts the following technical solution:
[0006] A single-component thermally conductive gel comprises the following raw materials by weight: 12-15 parts of vinyl silicone oil, 5-8 parts of side hydrogenated silicone oil, 2-5 parts of liquid metal, 60-65 parts of modified boron nitride thermally conductive filler, 3-5 parts of coupling agent and 1-2 parts of catalyst.
[0007] By adopting the above technical scheme, vinyl silicone oil: as the main base oil, provides the basic properties and viscosity of the thermally conductive gel. Side hydrogenated silicone oil: helps the vinyl silicone oil to form a gel structure during the preparation process and enhances the thermal conductivity. Liquid metal: provides better thermal conductivity, cooperates with the modified boron nitride thermal conductive filler to improve the overall thermal conductivity. Modified boron nitride thermal conductive filler: as the main thermal conductive filler, the modification improves the dispersibility and compatibility, forms a "percolation network", improves the thermal conductivity, and hinders the oil permeation rate. Coupling agent: promotes the adhesion between different components, improves the stability and thermal conductivity of the gel. Catalyst: accelerates the gel formation process and ensures the preparation rate of the thermally conductive gel. These components work together, the modified boron nitride thermal conductive filler cooperates with the liquid metal to improve the overall thermal conductivity of the thermally conductive gel; vinyl silicone oil and side hydrogenated silicone oil form a gel structure to enhance the thermal conductivity; coupling agent and catalyst promote the interaction between the components to ensure the stability and preparation rate of the gel. Therefore, the synergistic effect of each component makes the single-component thermal conductive gel prepared in the present application have the advantages of excellent thermal conductivity, high extrusion rate and low oil permeability.
[0008] Preferably, the vinyl silicone oil is divinyl polydimethylsiloxane, and the viscosity of the divinyl polydimethylsiloxane is 100 mPa·s and the vinyl content is 0.37 mmol / g.
[0009] Preferably, the viscosity of the hydrogenated silicone oil is 100 mPa·s, and the active hydrogen content is 0.1%.
[0010] Preferably, the liquid metal is composed of gallium-indium alloy, gallium-indium-tin alloy and gallium metal in a mass ratio of 6:3:0.5-1.
[0011] By adopting the above technical solution, gallium-indium alloy is the main liquid metal component in the thermally conductive gel, which has good thermal conductivity and can improve the thermal conductivity of the overall thermally conductive gel. Its liquid state helps to fill the tiny gaps in the thermally conductive gel and promote heat conduction. As one of the components of liquid metal, gallium-indium-tin alloy can help optimize the performance of liquid metal and improve the thermal conductivity of the overall thermally conductive gel. Gallium metal, as another component of liquid metal, adjusts the performance of the thermally conductive gel and enhances the thermal conductivity. These three liquid metal components cooperate with each other and work synergistically to provide excellent thermal conductivity, improve the overall thermal conductivity, and improve the thermal conductivity of the thermally conductive gel. When used in combination with modified boron nitride thermal conductive filler, the overall performance of the thermally conductive gel is further improved to form a more effective thermal conductive network. Therefore, the role of liquid metal in this application is to improve the thermal conductivity of the thermally conductive gel, and to work synergistically with other components to ensure that the thermally conductive gel has excellent thermal conductivity, high extrusion rate and low oil permeability.
[0012] Preferably, the method for preparing the modified boron nitride thermally conductive filler comprises the following steps:
[0013] S51, according to the mass fraction, placing 50 parts of boron nitride in 150-160 parts of 1 mol / L NaOH solution, pre-treating at 90°C for 4-5 hours, washing off the surface oil, filtering, and then placing the deoiled boron nitride in an ozonation treatment device for ozonation treatment for 2-3 hours, solid-liquid separation, to obtain ozonated modified boron nitride;
[0014] S52. Add 50 parts of ozonated modified boron nitride into a reactor containing 120 parts of 3-(isomethacryloyloxy)propyltrimethoxysilane and 300 parts of toluene according to their mass fractions, place in an oil bath at 92°C with stirring, and reflux the cold gel for 4-5 hours. Rinse the boron nitride treated with 3-(isomethacryloyloxy)propyltrimethoxysilane twice with ethanol, then wash once with distilled water, filter and dry to obtain a modified boron nitride thermal conductive filler.
[0015] By adopting the above technical scheme, the modified boron nitride thermal conductive filler prepared in the present application has the following effects and synergistic effects in the single-component thermal conductive gel: Improving dispersibility and compatibility: After being treated with ozonation and 3-(isobutyleneoxy)propyltrimethoxysilane, the surface of the boron nitride particles is oxidized and reacts with the organosilicon compound, thereby improving the hydrophobicity of boron nitride and its compatibility with the organosilicon compound, thereby improving the dispersibility and uniformity of the thermal conductive filler in the thermal conductive gel. Forming a "percolation network": The modified boron nitride thermal conductive filler interacts with other components to form a "percolation network" structure in the single-component thermal conductive gel, effectively improving the thermal conductivity of the thermal conductive gel and enhancing the conduction of heat. Reducing the oil permeability: The characteristics of the modified boron nitride thermal conductive filler can effectively hinder the seepage of free small molecules, reduce the oil permeability of the thermal conductive gel, and make the thermal conductive gel more stable and durable.
[0016] Preferably, the boron nitride is prepared by mixing boron nitride with a particle size of 2 μm and 30 μm in a mass ratio of 1:5.
[0017] By adopting the above technical solution, a boron nitride mixture prepared by mixing boron nitride with a particle size of 2μm and 30μm in a mass ratio of 1:5 has an important role and synergistic effect in a single-component thermally conductive gel, and its effects are as follows: Increase the packing density: Boron nitride particles with small particle sizes are adsorbed around large particle sizes under the action of electrostatic force, thereby increasing the packing density of the boron nitride thermally conductive filler. This helps to reduce the gaps between boron nitride particles and improve the compactness of the filler, thereby increasing the thermal conductivity of the single-component thermally conductive gel. Reduce phonon scattering: The addition of small particles reduces the phonon scattering caused by the interface, which is beneficial to the conduction of phonons inside the filler and helps to improve the thermal conductivity of the thermally conductive gel. Improve thermal conductivity: By mixing boron nitride with different particle sizes, the scattering obstacles in heat transfer can be effectively reduced, and the overall thermal conductivity of the modified boron nitride thermally conductive filler can be improved. This can significantly improve the thermal conductivity of the single-component thermally conductive gel, giving it better thermal conductivity. In summary, the role of mixing boron nitride of different particle sizes in a single-component thermally conductive gel is to increase the packing density, reduce phonon scattering and improve thermal conductivity. These effects work together synergistically to make the thermally conductive gel have better thermal conductivity.
[0018] Preferably, the ozone concentration during the ozonation treatment is 125-135 mg / L.
[0019] Preferably, the coupling agent is composed of hexadecyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane and methyltrimethoxysilane in a mass ratio of 2:7:2.
[0020] By adopting the above technical solution, the coupling agent can improve the compatibility between the boron nitride filler and other components such as silicone oil, which helps to improve the dispersibility of the modified boron nitride and make it more evenly dispersed in the gel, thereby enhancing the overall thermal conductivity of the gel. The functional groups in coupling agents such as hexadecyltrimethoxysilane and 3-(isobutyleneoxy)propyltrimethoxysilane can react chemically with the surface active sites of the modified boron nitride to form chemical bonds, thereby effectively combining the filler and silicone oil, enhancing the bonding force between the two, and improving the stability and thermal conductivity of the overall thermal conductive gel. The addition of a coupling agent can improve the extrusion rate of a single-component thermal conductive gel, so that the gel has better extrusion performance, which is beneficial to operation and application in the production process. In summary, the coupling agent in the present application is composed of hexadecyltrimethoxysilane, 3-(isobutyleneoxy)propyltrimethoxysilane and methyltrimethoxysilane, and plays a key role in the process of preparing a single-component thermally conductive gel, including enhancing dispersibility and compatibility, promoting the combination of filler and silicone oil, and adjusting extrusion performance. These effects work synergistically to provide a guarantee for the performance of the thermally conductive gel.
[0021] Preferably, the catalyst is a platinum catalyst, and the content of the platinum catalyst is 5ppm-8ppm based on the mass of platinum.
[0022] In a second aspect, the present application provides a method for preparing a single-component thermally conductive gel, using the following technical solution:
[0023] As a general technical concept, the present application also provides a method for preparing the above-mentioned one-component thermal conductive gel, comprising the following steps: S101, according to the mass fractions, vinyl silicone oil, side hydrogen silicone oil and coupling agent are put into a planetary mixer, and stirred and mixed evenly;
[0024] S102, adding 50% of modified boron nitride thermal conductive filler to the product of step S101, stirring at 55 rpm for 20-40 min, heating to 35° C., adding liquid metal and stirring at 70 rpm for 20-30 min, adding modified boron nitride thermal conductive filler and stirring at 55 rpm until uniform, and then adding catalyst and stirring at 35 rpm until uniform;
[0025] S103, evacuate the product of step S102 for 10-20 minutes, with a relative vacuum pressure of -0.1 MPa to -0.08 MPa, and let it stand for 30 minutes to obtain a single-component thermally conductive gel.
[0026] In summary, the beneficial technical effects of this application are:
[0027] 1. Excellent thermal conductivity: By using modified boron nitride thermal conductive filler and reasonably proportioned raw materials, the thermal conductive gel has excellent thermal conductivity, which is conducive to effectively conducting heat and improving thermal conduction efficiency.
[0028] 2. High extrusion rate: The gel has good extrusion performance and can quickly and stably form a heat-conducting medium through the extrusion equipment, thereby improving production efficiency.
[0029] 3. Low oil permeability: The addition of modified boron nitride thermal conductive filler can form a network structure, hinder the seepage of free small molecular substances, effectively reduce the oil permeability of the gel, and improve its stability and service life.
[0030] 4. Optimization of modified boron nitride thermal conductive filler: Through a special preparation method, the modified boron nitride thermal conductive filler has better dispersibility and compatibility during the preparation process, thereby improving the thermal conductivity of the overall thermal conductive gel.
[0031] 5. Excellent thermal conductivity: When boron nitride with different particle sizes is compounded, small-particle boron nitride is adsorbed around large-particle particles, reducing phonon scattering and increasing the packing density of the filler, thereby further improving the thermal conductivity of the thermally conductive gel. DETAILED DESCRIPTION
[0032] The implementation scheme of the present application will be described in detail below in conjunction with the examples, but those skilled in the art will understand that the following examples are only used to illustrate the present application and should not be considered to limit the scope of the present application. If the specific conditions are not specified in the examples, they are carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially. The melting point of gallium-indium alloy is 16°C, the melting point of gallium-indium-tin alloy is 11°C, and the melting point of gallium metal is 30°C.
[0033] Preparation Example 1 Preparation of modified boron nitride thermal conductive filler
[0034] The preparation method of modified boron nitride thermal conductive filler comprises the following steps:
[0035] S51. According to the mass fraction, 5 kg of boron nitride was placed in 15 kg of 1 mol / L NaOH solution, pretreated at 90 ° C for 4 hours, the surface oil was washed off, filtered, and the deoiled boron nitride was placed in an ozonation treatment device, and ozonation treatment was performed for 3 hours at an ozone concentration of 125 mg / L, and solid-liquid separation was performed to obtain ozonated modified boron nitride, wherein the boron nitride was prepared by mixing boron nitride with a particle size of 2 μm and 30 μm at a mass fraction ratio of 1:5;
[0036] S52. According to the mass fraction, add 5 kg of ozonated modified boron nitride into a reactor containing 12 kg of 3-(isomethacryloyloxy)propyltrimethoxysilane and 30 kg of toluene, oil bath at 92 ° C with stirring, cold gel reflux for 4 hours, then rinse the boron nitride treated with 3-(isomethacryloyloxy)propyltrimethoxysilane with ethanol twice, then wash it with distilled water once, filter it with suction, and dry it to obtain a modified boron nitride thermal conductive filler.
[0037] Preparation Example 2 Preparation of modified boron nitride thermal conductive filler
[0038] The preparation method of modified boron nitride thermal conductive filler comprises the following steps:
[0039] S51. According to the mass fraction, 5 kg of boron nitride was placed in 16 kg of 1 mol / L NaOH solution, pretreated at 90 ° C for 5 h, washed off the surface oil, filtered, and then the deoiled boron nitride was placed in an ozonation treatment device, and ozonated for 2 hours at an ozone concentration of 135 mg / L, and solid-liquid separation was performed to obtain ozonated modified boron nitride, wherein the boron nitride was prepared by mixing boron nitride with a particle size of 2 μm and 30 μm in a mass fraction ratio of 1:5;
[0040] S52. According to the mass fraction, add 5 kg of ozonated modified boron nitride into a reactor containing 12 kg of 3-(isomethacryloyloxy)propyltrimethoxysilane and 30 kg of toluene, oil bath at 92 ° C with stirring, cold gel reflux for 5 hours, then rinse the boron nitride treated with 3-(isomethacryloyloxy)propyltrimethoxysilane with ethanol twice, then wash it with distilled water once, filter it with suction, and dry it to obtain a modified boron nitride thermal conductive filler.
[0041] Preparation Example 3 Preparation of modified boron nitride thermal conductive filler
[0042] The preparation method of modified boron nitride thermal conductive filler comprises the following steps:
[0043] S51. According to the mass fraction, 5 kg of boron nitride was placed in 15.5 kg of 1 mol / L NaOH solution, pretreated at 90 ° C for 4.5 hours, washed off the surface oil, filtered, and then the deoiled boron nitride was placed in an ozonation treatment device, and ozonated for 2.5 hours at an ozone concentration of 130 mg / L, and solid-liquid separation was performed to obtain ozonated modified boron nitride, wherein the boron nitride was prepared by mixing boron nitride with a particle size of 2 μm and 30 μm in a mass fraction ratio of 1:5;
[0044] S52. According to the mass fraction, add 5 kg of ozonated modified boron nitride into a reactor containing 12 kg of 3-(isobutyleneoxy)propyltrimethoxysilane and 30 kg of toluene, oil bath at 92 ° C with stirring, cold gel reflux for 4.5 hours, then rinse the boron nitride treated with 3-(isobutyleneoxy)propyltrimethoxysilane with ethanol twice, then wash it with distilled water once, filter it with suction, and dry it to obtain a modified boron nitride thermal conductive filler.
[0045] Preparation of comparative example 1: Preparation of modified boron nitride thermally conductive filler
[0046] The same as Preparation Example 3, except that: the boron nitride has a particle size of 2 μm.
[0047] Preparation of Comparative Example 2 Preparation of Modified Boron Nitride Thermally Conductive Filler
[0048] The same as Preparation Example 3, except that: the boron nitride has a particle size of 30 μm.
[0049] Example 1
[0050] A single-component thermally conductive gel, comprising the following raw materials, by mass: 1.2 kg of vinyl silicone oil, 0.5 kg of side hydrogenated silicone oil, 0.2 kg of liquid metal, 6.0 kg of modified boron nitride thermally conductive filler, 0.3 kg of coupling agent, and 0.1 kg of catalyst, wherein the vinyl silicone oil is divinyl polydimethylsiloxane, the viscosity of the divinyl polydimethylsiloxane is 100 mPa·s, and the vinyl content is 0.37 mmol / g; the viscosity of the side hydrogenated silicone oil is 10 0mPa·s, the active hydrogen content is 0.1%, the liquid metal is composed of gallium-indium alloy, gallium-indium-tin alloy and gallium metal in a mass ratio of 6:3:0.5, the coupling agent is composed of hexadecyltrimethoxysilane, 3-(isobutyleneoxy)propyltrimethoxysilane and methyltrimethoxysilane in a mass ratio of 2:7:2, the catalyst is a platinum catalyst, and its content is 5ppm based on the mass of platinum; the modified boron nitride thermal conductive filler is the modified boron nitride thermal conductive filler prepared in Preparation Example 1;
[0051] The method for preparing the above-mentioned one-component thermally conductive gel comprises the following steps:
[0052] S101, according to the mass parts, vinyl silicone oil, side hydrogen silicone oil and coupling agent are put into a planetary mixer, and stirred and mixed evenly;
[0053] S102, adding 50% of modified boron nitride thermal conductive filler to the product of step S101, stirring at 55 rpm for 20 min, heating to 35° C., adding liquid metal and stirring at 70 rpm for 20 min, adding modified boron nitride thermal conductive filler and stirring at 55 rpm until uniform, and then adding catalyst and stirring at 35 rpm until uniform;
[0054] S103, evacuate the product of step S102 for 10 minutes, with a relative vacuum pressure of -0.1 MPa, and let it stand for 30 minutes to obtain a single-component thermally conductive gel.
[0055] Example 2
[0056] A single-component thermally conductive gel, comprising the following raw materials by mass: 1.5 kg of vinyl silicone oil, 0.8 kg of side hydrogenated silicone oil, 0.5 kg of liquid metal, 6.5 kg of modified boron nitride thermally conductive filler, 0.5 kg of coupling agent, and 0.2 kg of catalyst, wherein the vinyl silicone oil is divinyl polydimethylsiloxane, the viscosity of the divinyl polydimethylsiloxane is 100 mPa·s, the vinyl content is 0.37 mmol / g, and the viscosity of the side hydrogenated silicone oil is 1 00mPa·s, the active hydrogen content is 0.1%, the liquid metal is composed of gallium-indium alloy, gallium-indium-tin alloy and gallium metal in a mass ratio of 6:3:1, the coupling agent is composed of hexadecyltrimethoxysilane, 3-(isobutyleneoxy)propyltrimethoxysilane and methyltrimethoxysilane in a mass ratio of 2:7:2, the catalyst is a platinum catalyst, and its content is 8ppm based on the mass of platinum; the modified boron nitride thermal conductive filler is the modified boron nitride thermal conductive filler prepared in Preparation Example 2;
[0057] The method for preparing the above-mentioned one-component thermally conductive gel comprises the following steps:
[0058] S101, according to the mass parts, vinyl silicone oil, side hydrogen silicone oil and coupling agent are put into a planetary mixer, and stirred and mixed evenly;
[0059] S102, adding 50% of modified boron nitride thermal conductive filler to the product of step S101, stirring at 55 rpm for 40 min, heating to 35° C., adding liquid metal and stirring at 70 rpm for 30 min, adding modified boron nitride thermal conductive filler and stirring at 55 rpm until uniform, and then adding catalyst and stirring at 35 rpm until uniform;
[0060] S103, evacuate the product of step S102 for 20 minutes, with a relative vacuum pressure of -0.08 MPa, and let it stand for 30 minutes to obtain a single-component thermally conductive gel.
[0061] Example 3
[0062] A single-component thermally conductive gel, comprising the following raw materials by mass: 1.3 kg of vinyl silicone oil, 0.6 kg of side hydrogenated silicone oil, 0.35 kg of liquid metal, 6.3 kg of modified boron nitride thermally conductive filler, 0.4 kg of coupling agent, and 0.15 kg of catalyst, wherein the vinyl silicone oil is divinyl polydimethylsiloxane, the viscosity of the divinyl polydimethylsiloxane is 100 mPa·s, the vinyl content is 0.37 mmol / g, and the viscosity of the side hydrogenated silicone oil is 1 00mPa·s, the active hydrogen content is 0.1%, the liquid metal is composed of gallium-indium alloy, gallium-indium-tin alloy and gallium metal in a mass ratio of 6:3:0.8, the coupling agent is composed of hexadecyltrimethoxysilane, 3-(isobutyleneoxy)propyltrimethoxysilane and methyltrimethoxysilane in a mass ratio of 2:7:2, the catalyst is a platinum catalyst, and its content is 7ppm based on the mass of platinum; the modified boron nitride thermal conductive filler is the modified boron nitride thermal conductive filler prepared in Preparation Example 3;
[0063] The method for preparing the above-mentioned one-component thermally conductive gel comprises the following steps:
[0064] S101, according to the mass parts, vinyl silicone oil, side hydrogen silicone oil and coupling agent are put into a planetary mixer, and stirred and mixed evenly;
[0065] S102, adding 50% of modified boron nitride thermal conductive filler to the product of step S101, stirring at 55 rpm for 30 min, heating to 35° C., adding liquid metal and stirring at 70 rpm for 25 min, adding modified boron nitride thermal conductive filler and stirring at 55 rpm until uniform, and then adding catalyst and stirring at 35 rpm until uniform;
[0066] S103, evacuate the product of step S102 for 15 minutes, the relative vacuum pressure is -0.09 MPa, and stand for 30 minutes to obtain a single-component thermal conductive gel.
[0067] Example 4
[0068] The same as Example 3, except that the liquid metal is a gallium-indium alloy.
[0069] Example 5
[0070] The same as Example 3, except that the liquid metal is a gallium-indium-tin alloy.
[0071] Example 6
[0072] The same as Example 3, except that the liquid metal is gallium metal.
[0073] Comparative Example 1
[0074] The same as Example 3, except that the modified boron nitride thermally conductive filler is the modified boron nitride thermally conductive filler prepared in Comparative Example 1.
[0075] Comparative Example 2
[0076] The same as Example 3, except that the modified boron nitride thermally conductive filler is the modified boron nitride thermally conductive filler prepared in Comparative Example 2.
[0077] Comparative Example 3
[0078] The same as Example 3, except that an equal amount of boron nitride prepared by mixing boron nitride with a particle size of 2 μm and 30 μm in a mass ratio of 1:5 is used to replace the modified boron nitride thermal conductive filler prepared in Preparation Example 3.
[0079] Comparative Example 4
[0080] The same as Example 3, except that the coupling agent is hexadecyltrimethoxysilane.
[0081] Comparative Example 5
[0082] The same as Example 3, except that the coupling agent is 3-(isomethacryloyloxy)propyltrimethoxysilane.
[0083] Comparative Example 6
[0084] The same as Example 3, except that the coupling agent is methyltrimethoxysilane.
[0085] Comparative Example 7
[0086] The same as Example 3, except that the amount of liquid metal added is 0 kg.
[0087] Performance Testing
[0088] The single-component thermally conductive gels prepared in Examples 1 to 6 and Comparative Examples 1 to 7 were sampled and subjected to the following performance tests. The test results are shown in Table 1.
[0089] Thermal conductivity: Tested in accordance with ASTM D5470;
[0090] Extrusion rate: measured according to ASTM D2452-2015;
[0091] Oil seepage determination method: Take 10g of single-component thermal conductive gel, place it on filter paper, and spread it into a circular gel sample with a diameter of 3cm. After baking at 120℃ for 7 days, calculate the oil seepage area (the area of the circular gel sample with the largest area at the edge of the oil seepage);
[0092] The volume resistivity is tested according to ASTM D257;
[0093] Table 1 Performance test
[0094]
[0095]
[0096] Analyzing the data in Table 1, we can see that:
[0097] 1) The single-component thermally conductive gels prepared in Examples 1 to 3 have the advantages of excellent thermal conductivity, high extrusion rate and low oil permeability.
[0098] 2) The performance comparison analysis of the single-component thermally conductive gel prepared in combination with Examples 3 and 4-6 shows that the use of liquid metal composed of gallium-indium alloy, gallium-indium-tin alloy and gallium metal in a mass ratio of 6:3:0.8, and the synergistic effect between them, can provide excellent thermal conductivity, improve the overall thermal conductivity, and enhance the thermal conductivity effect of the thermally conductive gel. When used in combination with modified boron nitride thermally conductive filler, the overall performance of the thermally conductive gel is further improved to form a more effective thermally conductive network.
[0099] 3) The performance comparison analysis of the single-component thermally conductive gel prepared in combination with Example 3 and Comparative Examples 1-3 shows that the boron nitride is prepared by mixing boron nitride with a particle size of 2 μm and 30 μm in a mass ratio of 1:5, and after being treated with ozonation and 3-(isobutylene oxy)propyltrimethoxysilane, the surface of the boron nitride particles is oxidized and reacts with the organosilicon compound, thereby improving the hydrophobicity and compatibility of boron nitride with the organosilicon compound, thereby improving the dispersion and uniformity of the thermally conductive filler in the thermally conductive gel. Formation of a "percolation network": The modified boron nitride thermally conductive filler interacts with other components to form a "percolation network" structure in the single-component thermally conductive gel, effectively improving the thermal conductivity of the thermally conductive gel and enhancing the conduction of heat. Reduce oil permeability: The characteristics of the modified boron nitride thermally conductive filler can effectively hinder the seepage of free small molecules, reduce the oil permeability of the thermally conductive gel, and make the thermally conductive gel more stable and durable.
[0100] 4) The performance comparison analysis of the one-component thermally conductive gel prepared in combination with Example 3 and Comparative Examples 4 to Comparative Examples 6 shows that the coupling agent is composed of hexadecyltrimethoxysilane, 3-(isobutyleneoxy)propyltrimethoxysilane and methyltrimethoxysilane in a mass ratio of 2:7:2. By utilizing the synergistic effect between them, the addition of the coupling agent can improve the extrusion rate of the one-component thermally conductive gel, so that the gel has better extrusion performance, which is beneficial to the operation and application in the production process.
[0101] 5) The comparative analysis of the performance of the single-component thermally conductive gel prepared in Example 3 and Comparative Example 7 shows that the addition of liquid metal additives can significantly improve the thermal conductivity of the single-component thermally conductive gel.
[0102] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation modes of the present invention can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the scope of protection of the present application.
Claims
1. A single-component thermally conductive gel, characterized in that: The preparation material comprises the following raw materials by weight: 12-15 parts of vinyl silicone oil, 5-8 parts of side hydrogenated silicone oil, 2-5 parts of liquid metal, 60-65 parts of modified boron nitride thermal conductive filler, 3-5 parts of coupling agent, and 1-2 parts of catalyst; the liquid metal is composed of gallium-indium alloy, gallium-indium-tin alloy and gallium metal in a weight ratio of 6:3:0.5-1; the coupling agent is composed of hexadecyltrimethoxysilane, 3-(isobutyleneoxy)propyltrimethoxysilane and methyltrimethoxysilane in a weight ratio of 2:7:2; The preparation method of the modified boron nitride thermal conductive filler comprises the following steps: S51. According to the mass fraction, 50 parts of boron nitride are placed in 150-160 parts of 1 mol / L NaOH solution, pretreated at 90°C for 4-5 hours, the surface oil is washed off, filtered, and the deoiled boron nitride is placed in an ozonation treatment device for ozonation treatment for 2-3 hours, solid-liquid separation, to obtain ozonated modified boron nitride; the ozone concentration during the ozonation treatment is 125-135 mg / L; the boron nitride is prepared by mixing boron nitride with a particle size of 2 μm and 30 μm at a mass fraction ratio of 1:5; S52. Add 50 parts of ozonated modified boron nitride into a reactor containing 120 parts of 3-(isomethacryloyloxy)propyltrimethoxysilane and 300 parts of toluene according to their mass fractions, place in an oil bath at 92°C with stirring, and reflux the cold gel for 4-5 hours. Rinse the boron nitride treated with 3-(isomethacryloyloxy)propyltrimethoxysilane twice with ethanol, then wash once with distilled water, filter and dry to obtain a modified boron nitride thermal conductive filler.
2. A one-component thermally conductive gel according to claim 1, characterized in that: The vinyl silicone oil is divinyl polydimethylsiloxane, the viscosity of the divinyl polydimethylsiloxane is 100 mPa·s, and the vinyl content is 0.37 mmol / g.
3. A one-component thermally conductive gel according to claim 1, characterized in that: The viscosity of the hydrogen-containing silicone oil is 100 mPa·s, and the active hydrogen content is 0.1%.
4. A one-component thermally conductive gel according to claim 1, characterized in that: The catalyst is a platinum catalyst, and the content of the platinum catalyst is 5ppm-8ppm based on the mass of platinum.
5. A method for preparing the single-component thermally conductive gel according to any one of claims 1 to 4, characterized in that: The following steps are involved: S101, according to the mass parts, vinyl silicone oil, side hydrogen silicone oil and coupling agent are put into a planetary mixer, and stirred and mixed evenly; S102, adding 50% of the modified boron nitride thermal conductive filler to the product of step S101, stirring at 55 rpm for 20-40 min, heating to 35° C., adding liquid metal and stirring at 70 rpm for 20-30 min, adding the remaining modified boron nitride thermal conductive filler and stirring at 55 rpm until uniform, and then adding the catalyst and stirring at 35 rpm until uniform; S103, evacuate the product of step S102 for 10-20 minutes, the relative vacuum pressure is -0.1 MPa to -0.08 MPa, and let it stand for 30 minutes to obtain a single-component thermal conductive gel.
Citation Information
Patent Citations
High-heat-conductivity silicone grease and preparation method thereof
CN109438987A
Polydimethylsiloxane-based liquid metal bridged spherical boron nitride heat-conducting composite material as well as preparation method and application thereof
CN113337125A
High-thermal-conductivity non-stick pan coating and preparation method thereof
CN118290994A